Effect of Straw Mulch Thickness and KCL Fertilizer Dosage on Productivity of Shallots (Allium ascalonicum L.): Pengaruh Ketebalan Mulsa Jerami dan Dosis Pupuk KCL Terhadap Produktivitas Bawang Merah (Allium ascalonicum L.) - Putu Sugianto; Musrif Musrif (Program Studi Agroteknologi Fakultas Pertanian Universitas Dayanu Ikhsanuddin, 2021)
This study aims to determine; (1) Effect of straw mulch thickness on shallot plant productivity, (2) Effect of KCL fertilizer dosage on shallot plant productivity, (3) Effect of interaction between straw mulch thickness and KCL fertilizer dosage on shallot plant productivity. This research was conducted from March to May 2020 at Wanajati, Tampuna Village, Bungi District, Baubau City. The experimental design used was a randomized block design (RBD) with a factorial pattern consisting of two factors. The first factor consists of three levels, namely Tampa Mulch (T0), Mulch Thickness 1cm (T1), and Mulch Thickness 3cm (T2). The second factor is the KCL fertilizer dosage also consists of three levels, namely; TampaPupuk (P0), KCL fertilizer 0.5 g (P1), and KCL fertilizer 1.0 g. Based on the results of the study, the thickness of the mulch only had a significant effect on the number of leaves at the age of 2 MST, 4 MST and 6 MST and did not have an effect on the number of tubers, wet weight, dry weight and productivity of shallots while KCL fertilizer had a significant effect on the number of leaves, the number of tubers. , wet weight, dry weight and productivity of shallots. Keywords: Shallots, Thickness of mulch, KCl fertilizer